Electronic control seed-metering system for precision seeding maize based on fuzzy PID - Zhao, Xiaoshun; Zhao, Hongpeng; Wang, Zehe; Li, Jincai; Yu, Huali; Yan, Qing (International Journal of Agricultural and Biological Engineering, 2024)
Aiming at the problem of poor uniformity of maize sowing caused by ground wheel slip, an electronic control seed-metering system (ECSMS) for maize single seed precision sowing was designed and a mathematical model for motor control of the ECSMS was determined. The PID parameters were set by Z-N method and fuzzy control. The fuzzy PID control design and Simulink simulation were completed by MATLAB, which reduced response time of the system by 0.23 s and improved the control accuracy. Experiments on the JPS-12 test bench show that the qualification index (QI) of maize seed-metering device with the ECSMS increases by 4.47%, the multiples index (MI) decreases by 1.96%, the miss index (MIX) decreases by 2.81%, and the coefficient of variation (CV) of qualified seed spacing decreases by 5.06%, and the sowing uniformity has been greatly improved. Test results of the soil-tank test bench show that the system has good sowing uniformity and stability. And the QI is 96.74%, the MI is 2.15%, the MIX is 1.10%, and the CV of qualified seed spacing is 16.24%. Under different setting seed spacing and different sowing operation speed, the change range of seeding quality index was within 10%. The results of field sowing test show that the QI was 84.21%, the MI was 2.63%, the MIX was 7.89%, and the CV of qualified seed spacing was 22.15%, which meet the requirements of JB/T 10293-2013 ‘Specification for single seed planters (precision planters)’ and the agronomic requirements for maize precision sowing. The system runs stably and reliably in practical operation and has good operation performance. Key words: maize; seed-metering system; electronic control; precision sowing; parameters tuning; fuzzy PID control; simulink simulationDOI: 10.25165/j.ijabe.20241704.8247Citation: Zhao X S, Zhao H P, Wang Z H, Li J C, Yu H L, Yan Q. Electronic control seed-metering system for precision seeding maize based on fuzzy PID. Int J Agric & Biol Eng, 2024; 17(4): 217–226.